2020
DOI: 10.1080/17453674.2020.1730660
|View full text |Cite
|
Sign up to set email alerts
|

Patients undergoing shoulder arthroplasty for failed nonoperative treatment of proximal humerus fracture have low implant survival and low patient-reported outcomes: 837 cases from the Danish Shoulder Arthroplasty Registry

Abstract: Background and purpose — When nonoperative treatment of proximal humerus fracture (PHF) fails, shoulder arthroplasty may be indicated. We investigated risk factors for revision and evaluated patient-reported outcome 1 year after treatment with either stemmed hemiarthroplasty (SHA) or reverse total shoulder arthroplasty (RTSA) after previous nonoperative treatment of PHF sequelae. Patients and methods — Data were derived from the Danish Shoulder Arthroplasty Registry and included 837 shoulder arthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…However, the recent literature is inconclusive on gender driven differences in outcome. 28,46,47 Significant differences found by our study are in concordance with the literature. However, for both RSA and HA, some studies found superior objective outcomes compared with ours.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the recent literature is inconclusive on gender driven differences in outcome. 28,46,47 Significant differences found by our study are in concordance with the literature. However, for both RSA and HA, some studies found superior objective outcomes compared with ours.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with a previous osteosynthesis of the shoulder and/or a delay in presentation to the emergency department of more than 1 month were also excluded. 28,29 Patients with a glenoid bone defect greater than 30% or more than 15 degrees retroversion of the glenoid were excluded. Informed consent was obtained from all individual participants.…”
Section: Methodsmentioning
confidence: 99%
“… 95 Other time points consisted of fractional time points, for example, 2.5, 7.3, etc. 23-25 , 43 , 47 , 64 , 81 …”
Section: Resultsmentioning
confidence: 99%
“…Incomplete PROM data is a common issue that affects other regional and national registries, [38][39][40][41][42][43][44][45][46][47] reflecting the difficulty in obtaining complete patient data even when multilevel data collection systems are put in place. The finding that incomplete data was slightly more likely to be an issue in male patients with rotator cuff pathology may be of use in identifying patients that are "at risk" of incomplete data and directing more resources at them to ensure the data is correctly completed.…”
Section: Strengths and Limitationsmentioning
confidence: 99%